Test-retest reliability and concurrent validity of photoplethysmography finger sensor to collect measures of heart rate variability - Rogers, D. W.; Himariotis, A. T.; Sherriff, T. J.; Proulx, Q. J.; Duong, M. T.; Noel, S. E.; Cornell, D. J. (Sports, 2025)
The purpose of the current study was to determine the test-retest reliability and concurrent validity of a photoplethysmography (PPG) finger sensor when collecting heart rate variability (HRV) metrics in reference to electrocardiography (ECG) and heart rate monitor (HRM) devices. Five minutes of R-R interval data were collected from 45 participants (23 females; age: 23.13 ± 4.45 yrs; body mass index: 25.39 ± 4.13 kg/m2) in the supine and seated positions in testing sessions 48 h apart. Moderate-to-excellent test-retest reliability of the HRV data collected from the PPG sensor was identified (ICC2,1 = 0.60-0.93). Additionally, similar standard errors of the mean, coefficient of variation, and minimal detectable change metrics were observed across all devices. Statistically significant (p < 0.05) differences were identified in the HRV data between the PPG sensor and ECG and HRM devices; however, these differences were interpreted as trivial-to-small (g = 0.00-0.59). Further, the PPG sensor tended to only overestimate HRV metrics by <0.5 ms and near perfect relationships (r = 0.91-1.00) and very large-to-near perfect agreement (CCC = 0.81-1.00) were identified between collection methods. The PPG sensor demonstrated adequate test-retest reliability and concurrent validity in both the supine and seated resting positions.